Institutional Problems of the Russian Model of Social Partnership Formation - A. A. Barabanov; E. M. Proshina (Управленческое консультирование)
Key problem of social partnership is ensuring stable development of society without social shocks. In the conditions of development of market economy, emergence of socially responsible business need of effective coordination of  interests of work and the capital becomes obvious. Social  partnership gives a unique opportunity of constructive dialogue and  allows prevent growth of social tension. In a number of foreign  countries the models of social partnership defining an order of  interaction of labor unions, associations of employers and the state.  The institute of social partnership still passes the formation period in  Russia. Emergence of the Russian model of social partnership is real  strategic prospect, which will fully allow realizing the principles of the social state and will open a way to new type of interaction between society and the state.